1979
DOI: 10.1073/pnas.76.12.6326
|View full text |Cite
|
Sign up to set email alerts
|

Organization of spacer DNA in chromatin.

Abstract: Detailed analysis of the DNA fragment patterns produced by DNase I digestion of yeast, HeLa, and chicken erythrocyte nuclei reveals surprising features of nucleosome phasing. First, the spacer regions in phased yeast chromatin must be of lengths (lOi + 5) base pairs, where m = 0, 1, 2,2.... This feature is not seen in parallel studies of chicken erythrocyte chromatin. The 5-base pair increment in the yeast spacer imposes interesting restraints on the higher order structure of yeast chromatin. Second DNase I di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
54
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 20 publications
8
54
0
Order By: Relevance
“…Finally, we note that earlier work has shown that yeast exhibits a very tight nucleosomal organization, with adjacent nucleosomes placed on opposite sides of the DNA helix due to the offset of one-half a helical turn (8)(9)(10)(11). Our results therefore suggest that this type of nucleosomal arrangement might be critical for efficient chromatin transcription by RNA polymerase II.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Finally, we note that earlier work has shown that yeast exhibits a very tight nucleosomal organization, with adjacent nucleosomes placed on opposite sides of the DNA helix due to the offset of one-half a helical turn (8)(9)(10)(11). Our results therefore suggest that this type of nucleosomal arrangement might be critical for efficient chromatin transcription by RNA polymerase II.…”
Section: Discussionmentioning
confidence: 56%
“…A central outstanding question is to what extent the nucleosomal arrangement affects Pol II transcription behavior. This arrangement might be particularly important in budding yeast, an organism with a compact genome with short internucleosomal distances (8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Considering a 1-to 2-bp overstretching effect of nucleosome DNA (33,36), the S. pombe genome displays a preferential linker length form of ∼10n + 4/5 bp. Because linker length is closely related to the high-order chromatin structure (37,38), this implies that these two genomes may share some similar aspects in high-order chromatin structure, regardless of the evolutionary divergence and distinctions in nucleosome formation between the species.…”
Section: Significancementioning
confidence: 99%
“…Gel electrophoresis of the DNA in denaturing conditions shows a ladder of discrete fragments extending up to or into dimer-size DNA. This observation was made for yeast, HeLa cells and chicken erythrocyte chromatin digested with DNase I (Lohr et al, 1977; Holde, 1979); rat thymus chromatin digested with Serratia marcescens nuclease (Pospelov et al, 1979); Drosophila chromatin digested with micrococcal nuclease (Karpov et al, 1982); and chicken erythrocyte (Riley and Weintraub, 1978), rat liver 1Present address: Department of Biology, Massachusetts Institute of Technology, Cambridge, MA 02139, USA. *To whom reprint requests should be sent.…”
Section: Introductionmentioning
confidence: 99%